2017
DOI: 10.5296/jad.v3i2.11491
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Financial and Non-Financial Compensation on Professionalism and Lecturers Performance: Evidence from Makassar Private Universities (Indonesia)

Abstract: This study aimed to test empirically the effect of financial and non financial compensation on professionalism and lecturer's performance. The study population was all lecturers who are certified, public and private lecturers at the private universities in Makassar (Indonesia). Stratified proportional random sampling was used to obtain the total sample of 111 lecturers'. Covariance-based SEM (SEMPLS) with a WarpPLS 5.0 used in this study. The results of the study provide evidence that financial and non financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In table 3, the independent variable (i.e Compensation) contributed positively and statistically to motivation of employees at a low relationship. The result is in consistence with empirical findings of Idris et al (2017) and Mardiyanti et al (2018) who noted that compensation management acts as an antidote to the motivation of an employee that invariably transforms the performance of the employees' which also translates to positive organizational outcome.…”
Section: Resultssupporting
confidence: 86%
“…In table 3, the independent variable (i.e Compensation) contributed positively and statistically to motivation of employees at a low relationship. The result is in consistence with empirical findings of Idris et al (2017) and Mardiyanti et al (2018) who noted that compensation management acts as an antidote to the motivation of an employee that invariably transforms the performance of the employees' which also translates to positive organizational outcome.…”
Section: Resultssupporting
confidence: 86%
“…98). Financial rewards or compensation can consist of direct financial compensation (in the form of cash payments received directly in salary/wages, economic benefits, bonuses, and commissions), and indirect financial compensation is the entire award excluding direct financial compensation (Idris et al, 2017). Financial rewards also mean those which satisfy the employees by providing rewards in terms of money (Mendis, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the study showed that both financial and non-financial remuneration had a significant impact on the lecturers' professionalism. The study further showed that financial compensation had a positive effect on the lecturers' performance but non-financial compensation did not (Idris et al, 2017). So, the lecturers' performance was only influenced by financial compensation but their behaviour was affected by both financial and non-financial compensation.…”
Section: Synthesis and Critical Evaluation Of The Literaturementioning
confidence: 82%
“…A study was conducted to test the effect of financial and non-financial remuneration on lecturers' performance and professionalism in Asia (Idris, Hamzah, Sudirman, & Hamid, 2017). The results of the study showed that both financial and non-financial remuneration had a significant impact on the lecturers' professionalism.…”
Section: Synthesis and Critical Evaluation Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation